Pendampingan Optimalisasi Penggunaan Metode Sorogan dalam Desain pembelajaran Maharoh qiro'ah di Asrama Dar Al-‘Ulum Assunniyyah - Nafsah, Nor Holis bin; Musthofa, Muchammad Khoirudin (INAIFAS Press, 2023)
One of the keys to success in learning a foreign language, such as Arabic, is optimizing the use of appropriate and correct methods. This research will explain the process of mentoring and optimizing the use of the sorogan method in maharoh qiro'ah learning design at the Dar Al-'Ulum Assunniyyah Dormitory. and by applying this method, it is hoped that it can train students to improve their mastery of Arabic grammar, making it easier to read and understand the terms of Arabic grammar well. The research method used in this research is a qualitative method. This research concludes that the sorogan method provides maximum results in increasing interest in learning and the ability of Dar Al-'Ulum Assunniyyah Dormitory students in the aspect of maharah Qiro'ah